Computational study of oxynitride based strong materials - Okeke, Onyekwelu Uzodinma (My University, 2010)
A spinel oxynitride material in the form M3NO3 (M = B, Al, Ga, or In) is considered to be derived from a reaction of the formMN +M2O3!M3NO3. Various possible phases ofMN and M2O3 that could lead to M3NO3 oxynitride spinel material have been considered in the work. The structural, electronic, elastic properties and the relative stabilities of the bulk and the nature of the resulting vacancies or defect-related properties of these oxynitride spinel structures are investigated using ab-initio or first principles electronic structure methods based on density functional theory (DFT). The bulk oxynitride spinel structure containing B and Al atoms exhibit higher resistance to compression and shear than those containing Ga and In atoms and therefore, these are suggested to be potentially important hard materials possibly formed under extreme conditions. Calculated energetics of the proposed reaction favor the formation of oxynitride spinels containing Ga and In with such materials having potentially significant optoelectronic applications. From results on defective oxynitride systems, with a vacancy at octahedral or tetrahedral sites, it is suggested that the structural stability of the oxynitride spinel materials could be lowered. In this thesis, a series of Tersoff empirical potentials for the bulk oxynitride spinel systems is proposed and tested by calculating the structural and elastic properties of the binary nitrides and M3NO3 oxynitride spinels using molecular dynamics simulation. The apparent success of treating some binary nitride systems using the Tersoff potential is used as a way forward to obtain a new parameter set that incorporates atomic features into a series of Tersoff potential for ternary oxynitrides spinel phases. The different thermodynamic properties of these oxynitride structure for varying temperature are also predicted such as the Debye temperature, thermal expansion co-efficient and specific heat. It is suggested that these materials will have thermal properties comparable to their binary nitride counterparts.